Metal-doped carbon-coated graphite composite material as well as preparation method and application thereof
Through the heat treatment of polymer carbon sources and graphite and doping of transition metal salts, metal-doped carbon-coated graphite composites are prepared, solving the problems of poor structure and chemical stability of existing graphite negative electrode materials, and achieving high-rate performance and fast charging capabilities.
Patent Information
- Application Number
- CN202411932754.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-21
AI Technical Summary
The existing metal-doped graphite negative electrode materials have poor structural stability and chemical stability, making it difficult to meet the needs of fast charging and high energy density of lithium-ion batteries.
By mixing the polymer carbon source with graphite for the first heat treatment, a carbon-coated graphite material is formed, and then mixed with the transition metal salt for the second heat treatment, a metal-doped carbon-coated graphite composite material is prepared.
This method effectively improves the rate performance and chemical stability of the material, enhances the fast charging capability of graphite, and is suitable for the negative electrode material of lithium-ion batteries.
Smart Images

Figure CN119660732A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal-doped carbon-coated graphite composite material and a preparation method and application thereof. Background Art
[0002] Graphite is currently the most widely used and practical negative electrode material for lithium-ion batteries due to its advantages such as reversible cycling, stable cycle life, good electronic conductivity, and easy processing. However, graphite may not meet the growing performance requirements of lithium-ion batteries due to its relatively low theoretical capacity (about 372 mAh / g) and poor fast charging performance. During fast charging, the slow kinetics of lithium insertion at the graphite-electrolyte interface causes the anode voltage to drop below 0 V, resulting in lithium plating, which may lead to capacity loss, dendrite growth, short circuits, and serious safety issues. In addition, the fast charging capability of graphite is limited by the narrow interlayer spacing (0.335 nm), the limited number of lithium ion insertion sites on the basal plane, and the long interlayer diffusion distance. In order to achieve widespread use in electric vehicles, graphite-based lithium batteries need to increase the charging speed while meeting the requirements of energy density, safety, production cost, cycle life, and cycle stability.
[0003] A Chinese patent document with publication number CN 116588924 A discloses a method for preparing a high-energy-density fast-charging negative electrode material, the preparation method comprising: (1) mixing asphalt, an organic solvent, a metal catalyst, and an organic metal compound to obtain a coating liquid; (2) mixing oxidized natural graphite and the coating liquid, introducing sulfur dioxide gas, and obtaining asphalt / catalyst / metal oxide coated natural graphite material after reaction; (3) carbonizing the asphalt / catalyst / metal oxide coated natural graphite material in a mixed gas to obtain phosphorus-doped amorphous carbon coated natural graphite; the patent claims that the high-energy-density fast-charging negative electrode material prepared by it can solve the problems of low first discharge specific capacity and poor cycle performance of graphite negative electrode materials in the prior art. However, in fact, the capacity, rate performance and cycle life of the negative electrode material still need to be improved. In addition, the phosphine gas used in the preparation process is highly toxic and dangerous, and is not suitable for industrial production.
[0004] A Chinese patent document with publication number CN 118658989 A discloses a new type of single-atom doped graphite negative electrode material for lithium-ion batteries and its preparation method. The preparation method mainly involves doping transition metal single atoms with graphite. The obtained natural graphite negative electrode material effectively increases the negative electrode lithium storage capacity and greatly improves the specific capacity. When used in lithium-ion batteries, it can greatly improve the specific capacity, cycle stability, and fast charging performance of lithium batteries. However, in the process of preparing the precursor mixture, the preparation method has high requirements. If the dispersion and uniformity of the precursor are not good, the uniformity of the graphite coating will be greatly affected. Uneven coating will lead to inconsistent conductivity of the material as a whole. The increased resistance in some areas will affect the transmission speed of electrons and reduce the rate performance of the battery. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of poor structural stability and chemical stability of existing metal-doped graphite negative electrode materials, and to provide a metal-doped carbon-coated graphite composite material and a preparation method and application thereof. The metal-doped carbon-coated graphite composite material of the present invention has good rate performance.
[0006] The present invention solves the above technical problems through the following technical solutions:
[0007] The present invention provides a method for preparing a metal-doped carbon-coated graphite composite material, which comprises the following steps:
[0008] (1) subjecting the first mixed solution to a first heat treatment to obtain a carbon-coated graphite material;
[0009] The first mixed solution comprises a carbon source, graphite and a first solvent, wherein the carbon source is a high molecular polymer carbon source, and the first solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent;
[0010] The mass ratio of the graphite to the carbon source is 100:(1-10);
[0011] (2) subjecting the second mixed solution to a second heat treatment to obtain a metal-doped carbon-coated graphite composite material;
[0012] The second mixed solution includes the carbon-coated graphite material, a transition metal salt and water;
[0013] The mass ratio of the carbon-coated graphite material to the transition metal salt is 100:(0.7-8).
[0014] In the present invention, in step (1), the polymer carbon source is conventional in the art. In some embodiments, the polymer is one or more of polyacrylic acid, polystyrene, polyvinyl alcohol, polyamide, polymethyl methacrylate, polytetrafluoroethylene and polyurethane.
[0015] In some embodiments, the molecular weight of the high molecular weight polymer carbon source is 10,000-100,000, for example, 30,000.
[0016] In the present invention, the high molecular polymer carbon source can be commercially available or prepared by the following method.
[0017] In some of the schemes, the preparation method of polyacrylic acid includes: mixing acrylic acid monomer, a third solvent and an initiator and reacting them to obtain polyacrylic acid; the second solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent.
[0018] In some embodiments, the initiator is preferably one or more of ammonium persulfate, potassium persulfate, azobisisobutyronitrile, and benzoyl peroxide.
[0019] In some embodiments, the alcohol organic solvent is methanol and / or ethanol.
[0020] In some embodiments, the ketone organic solvent is methyl ethyl ketone.
[0021] In some embodiments, the ether organic solvent is ethylene glycol monomethyl ether.
[0022] In some embodiments, the second solvent is preferably deionized water.
[0023] In some of the schemes, the reaction temperature is 60-90°C.
[0024] In some of the schemes, the reaction time is 2 to 6 hours.
[0025] In some of the schemes, after the reaction is completed, filtering and drying steps are further included; the filtration is preferably suction filtration; the drying temperature is preferably 60-90° C.; the drying time is preferably 15-25 h.
[0026] In the present invention, the carbon source may be a high molecular polymer carbon source material itself or a solution formed by mixing a high molecular polymer carbon source with a solvent.
[0027] In some of the schemes, the carbon source is a polymer carbon source solution formed by a polymer carbon source and a third solvent, and the third solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent; the alcohol organic solvent is preferably methanol and / or ethanol; the ketone organic solvent is preferably methyl ethyl ketone; the ether organic solvent is preferably ethylene glycol monomethyl ether;
[0028] Preferably, the content of the polymer carbon source in the polymer carbon source solution is 30-40%, for example 30%, where % refers to the mass proportion of the polymer carbon source in the polymer carbon source solution.
[0029] In some of the schemes, in step (1), the mass ratio of the graphite to the carbon source is 100:(2-7), preferably 100:(2-5), for example 50:1.67 or 50:3.34.
[0030] The inventors found in experiments that if the amount of polymer carbon source added is too much, the carbon coating layer will be too thick, the carbonization process will be incomplete, and the conductivity of the polymer carbon source will be poor, resulting in poor rate performance of the metal-doped carbon-coated graphite composite material; if the amount of polymer carbon source added is too little, it will be difficult to evenly cover the surface of the graphite particles, resulting in inconsistent coating thickness. Uneven coating will cause fluctuations in the thermal stability of the material, and will also cause agglomeration between graphite particles and shedding or damage of the coating during use.
[0031] In some of the schemes, in step (1), the graphite is spherical graphite, and the D50 particle size of the spherical graphite is preferably 4-20 μm, and more preferably 6-10 μm.
[0032] In some of the embodiments, the tap density of the spherical graphite is 0.6-1.0 g / cm 3 , preferably 0.7~0.9g / cm 3 .
[0033] In some of the embodiments, the specific surface area of the spherical graphite is 6.0 to 15.0 m 2 / g, preferably 10.0~13.0m 2 / g.
[0034] In some of the embodiments, the fixed carbon content of the graphite is preferably ≥ 99.95%.
[0035] In some of the schemes, in step (1), the graphite is natural graphite or artificial graphite.
[0036] In some of the schemes, in step (1), the first solvent is conventional in the art, such as deionized water.
[0037] In some of the schemes, in step (1), the mass ratio of the first solvent to the graphite is (0.5-10):1, for example, 1:1.
[0038] In some of the schemes, in step (1), the method for preparing the first mixed solution includes: mixing the carbon source, the graphite and the first solvent and then stirring.
[0039] In some of the solutions, the stirring speed is 200-600 rpm, preferably 300-500 rpm.
[0040] In some embodiments, the stirring time is 30 to 120 minutes, for example, 90 minutes.
[0041] In some of the schemes, in step (1), the temperature of the first heat treatment is 1000-1500°C, preferably 1000-1200°C, for example 1150°C.
[0042] The inventors found in experiments that when the temperature of the first heat treatment is lower than 1000°C, polyacrylic acid will form a discontinuous and uneven carbon layer, resulting in poor contact between particles and affecting conductivity; when the temperature of the first heat treatment is higher than 1500°C, the carbon layer will be too dense, affecting the embedding and extraction of lithium ions and reducing the electrochemical performance.
[0043] In some of the schemes, in step (1), the heating of the first heat treatment is a two-stage heating, wherein the first stage heating is preferably from room temperature to 900-1300°C, for example, 1080°C; and the second stage heating is preferably from 900-1300°C to 1000-1500°C, for example, 1150°C.
[0044] In some of the schemes, the heating rate of the first stage is preferably 3-25°C / min, such as 4°C / min; the heating rate of the second stage is preferably 2-10°C / min, such as 7°C / min.
[0045] In some of the schemes, in step (1), the first heat treatment is heated to the final temperature and the holding time is 6 to 10 hours, for example 8 hours.
[0046] In some of the schemes, in step (1), the first heat treatment is performed in an inert protective gas, and the protective gas is conventional in the art, such as nitrogen or argon.
[0047] In some of the schemes, in step (1), the mixed solution further includes a drying step before the first heat treatment.
[0048] The drying is conventional in the art. Preferably, in some embodiments, the drying is spray drying.
[0049] In some of the schemes, the spray drying adopts a high-speed centrifugal spray dryer; the inlet temperature of the high-speed centrifugal spray dryer is preferably 50~400℃, more preferably 100~300℃, for example 200℃; the outlet temperature of the high-speed centrifugal spray dryer is preferably 50~200℃, more preferably 50~100℃, for example 150℃; the rotation speed of the high-speed centrifugal spray dryer is preferably 5000~40000rpm, more preferably 10000~30000 rpm, for example 20000rpm.
[0050] In some of the schemes, in step (2), the mass ratio of the carbon-coated graphite material to the transition metal salt is 100:(0.8-3), for example, 50:0.45 or 50:0.9.
[0051] In some of the schemes, in step (2), the transition metal salt is a transition metal sulfate, a transition metal chloride or an ammonium salt of a transition metal.
[0052] In some embodiments, the transition metal sulfate is preferably one or more of nickel sulfate, cobalt sulfate, iron sulfate or titanium sulfate.
[0053] In some embodiments, the chloride salt of the transition metal is preferably titanium tetrachloride.
[0054] In some embodiments, the ammonium salt of the transition metal is preferably ammonium molybdate.
[0055] In some of the schemes, in step (2), the method for preparing the second mixed solution includes: mixing the transition metal salt with the water to obtain a solution of the transition metal salt, and mixing the solution of the transition metal salt with the carbon-coated graphite material to obtain the second mixed solution.
[0056] In some of the schemes, the carbon-coated graphite material and the solution of the transition metal salt are mixed by stirring. The stirring and mixing is conventional mechanical stirring in the art, and the stirring speed is preferably 200-600 rpm, more preferably 300-500 rpm; the stirring time is preferably 30-120 min, for example 90 min;
[0057] In some of the schemes, the content of the transition metal salt in the transition metal salt solution is 2.5-7%, for example 3% or 6%, where % refers to the mass proportion of the transition metal salt in the transition metal salt solution.
[0058] In some of the schemes, in step (2), the temperature of the second heat treatment is 800-1500°C, preferably 1000-1200°C, for example 1150°C.
[0059] In some of the schemes, in step (2), the heating of the second heat treatment is a two-stage heating, wherein the first stage heating is preferably from room temperature to 700-1200°C, for example, 1080°C; the second stage heating is preferably from 700-1200°C to 800-1500°C, for example, 1150°C.
[0060] In some of the schemes, the heating rate in the first stage is preferably 3-25°C / min, such as 4°C / min.
[0061] In some of the schemes, the heating rate of the second stage is preferably 2-10°C / min, such as 7°C / min.
[0062] In some of the schemes, in step (2), the second heat treatment is heated to the final temperature and the holding time is 6 to 10 hours, for example 8 hours.
[0063] In some of the schemes, in step (2), the second heat treatment is performed in an inert protective gas, and the protective gas is conventional in the art, such as nitrogen or argon.
[0064] The second heat treatment of the present invention can not only dope the carbon-coated graphite material with transition metal elements, but also make the carbon coating layer more complete, reduce pores, and help improve the stability of the carbon coating layer.
[0065] In some embodiments, in step (2), the second heat treatment further includes a drying step before the second heat treatment.
[0066] The drying is conventional in the art. In some embodiments, the drying is spray drying.
[0067] In some of the schemes, the spray drying adopts a high-speed centrifugal spray dryer; the inlet temperature of the high-speed centrifugal spray dryer is preferably 50~400℃, more preferably 100~300℃, for example 200℃; the outlet temperature of the high-speed centrifugal spray dryer is preferably 50~200℃, more preferably 50~100℃, for example 150℃; the rotation speed of the high-speed centrifugal spray dryer is preferably 5000~40000 rpm, more preferably 10000~30000 rpm, for example 20000 rpm.
[0068] In some embodiments, in step (2), the second heat treatment further includes a screening step.
[0069] In some of the schemes, the sieve is 300-350 mesh.
[0070] In some of the solutions, the step of mixing the materials before screening can improve the problem of easy clogging of the screen due to uneven particle size of the materials. Preferably, the mixing method comprises: placing the material obtained by the second heat treatment in a mixer for mixing, and the frequency of the mixer is 20-30 Hz, for example, 25 Hz.
[0071] The present invention also provides a metal-doped carbon-coated graphite composite material prepared by the above-mentioned method for preparing the metal-doped carbon-coated graphite composite material.
[0072] In some of the embodiments, the particle size of the metal-doped carbon-coated graphite composite material is 7-15 μm, such as 7.4 μm, 7.5 μm, 7.6 μm or 13.7 μm.
[0073] The present invention also provides a use of the metal-doped carbon-coated graphite composite material as a negative electrode material in a lithium-ion battery.
[0074] The positive and progressive effects of the present invention are:
[0075] The preparation method of the metal-doped graphite composite material of the present invention first uses a high molecular polymer solution to coat the graphite, which can effectively reduce the surface defects of natural graphite and coat it more evenly. After the first heat treatment, a highly cross-linked carbon structure is formed on the surface of the graphite, making the overall structure more stable; then it is coated with a transition metal salt solution, and after the second heat treatment, the metal elements are distributed in the carbon structure on the surface, thereby increasing its fast charging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1 This is a SEM image of the metal-doped carbon-coated graphite composite material of Example 1 of the present invention at a magnification of 500 times.
[0077] Figure 2 This is a SEM image of the metal-doped carbon-coated graphite composite material of Example 1 of the present invention at a magnification of 1000 times. DETAILED DESCRIPTION
[0078] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0079] Example 1
[0080] (1) 3 kg of acrylic acid, 7 kg of deionized water and 0.015 kg of ammonium persulfate were added to a three-necked flask equipped with a magnetic stirrer, a thermometer and a reflux condenser, stirred to fully dissolve, and then reacted in an oil bath at 80° C. for 4 hours. After the reaction was completed, heating was stopped, and the mixture was cooled to room temperature. Unreacted acrylic acid monomer and ammonium persulfate residue were filtered out by a suction filter, and the filtrate was transferred to a vacuum drying oven and dried at 60° C. for 24 hours to obtain a dry polyacrylic acid solid, the molecular weight of which was 30,000.
[0081] Deionized water and polyacrylic acid solid are mixed to prepare a 30% polyacrylic acid solution;
[0082] (2) 50 kg of fixed carbon content is 99.99%, D50 particle size is 6.5 μm, and tap density is 0.79 g / cm 3 , specific surface area is 11.85m 2 / g natural graphite, 5.56kg polyacrylic acid solution with a concentration of 30%, and 50kg deionized water were mixed at a speed of 300rpm for 90min;
[0083] (3) Drying the mixed slurry using a high-speed centrifugal spray dryer at an inlet temperature of 200°C, an outlet temperature of 150°C, and a rotation speed of 20,000 rpm to obtain a coated natural graphite negative electrode material; then heating the obtained 7 μm coated natural graphite negative electrode material from room temperature to 1080°C at a heating rate of 4°C / min under a nitrogen atmosphere, and then heating it to 1150°C at a heating rate of 7°C / min, and keeping the temperature for 8 hours. After carbonization and cooling, a carbon-coated graphite material is obtained;
[0084] (4) 1.05 kg of ammonium molybdate and 33.95 kg of deionized water were mixed to obtain a 3% ammonium molybdate solution; 15 kg of the solution and 50 kg of carbon-coated graphite material were mixed at a rotation speed of 300 rpm for 90 min;
[0085] Then, spray drying is performed in the same process as step (3); then, in a nitrogen atmosphere, the temperature is increased from room temperature to 1080° C. at a heating rate of 4° C. / min, and then to 1150° C. at a heating rate of 7° C. / min, and the temperature is kept at this temperature for 8 hours. After cooling, a transition metal-doped carbon-coated graphite material is obtained;
[0086] (5) Finally, the transition metal-doped carbon-coated graphite material is mixed in a solid phase mixer at 25 Hz to make the material evenly distributed, and then passed through a 350-mesh sieve to obtain the final metal-doped carbon-coated graphite composite material. The D50 of the metal-doped carbon-coated graphite composite material is 7.4 μm.
[0087] Example 2
[0088] This embodiment is basically the same as embodiment 1, except that in step (1) of this embodiment, the fixed carbon content of natural graphite is 99.99%, D50=13 μm, and the specific surface area is 7.4 m 2 / g, tap density is 0.79g / cm 3 .
[0089] The D50 of the metal-doped carbon-coated graphite composite material of this embodiment is 13.7 μm.
[0090] Example 3
[0091] This embodiment is basically the same as Embodiment 1, except that in step (2) of this embodiment, the mass of the polyacrylic acid solution is 11.12 kg.
[0092] The metal-doped carbon-coated graphite composite material of this embodiment has a D50 of 7.6 μm.
[0093] Example 4
[0094] This embodiment is basically the same as embodiment 1, except that in step (4) of this embodiment, molybdate is replaced by nickel sulfate.
[0095] The metal-doped carbon-coated graphite composite material of this embodiment has a D50 of 7.4 μm.
[0096] Example 5
[0097] This embodiment is basically the same as Embodiment 1, except that in step (4) of this embodiment, the concentration of the ammonium molybdate solution is 6%.
[0098] The metal-doped carbon-coated graphite composite material of this embodiment has a D50 of 7.5 μm.
[0099] Comparative Example 1
[0100] The preparation process is basically the same as that in Example 1, with the only difference being that in step (1), the polyacrylic acid coating agent is replaced with asphalt (softening point 200° C.).
[0101] The metal-doped carbon-coated graphite composite material of this comparative example has a D50 of 7.3 μm.
[0102] Comparative Example 2
[0103] 1.05 kg of ammonium molybdate and 33.95 kg of deionized water were mixed to obtain a 3% ammonium molybdate solution;
[0104] The ammonium molybdate solution was mixed with 50 kg of fixed carbon content of 99.99%, D50 particle size of 6.5 μm, and tap density of 0.79 g / cm 3 , specific surface area is 11.85m2 / g of natural graphite were mixed evenly at a rotation speed of 300 rpm, and the mixed slurry was dried using a high-speed centrifugal spray dryer with an inlet temperature of 200°C, an outlet temperature of 150°C, and a rotation speed of 20000 rpm;
[0105] The dried material was then heated from room temperature to 1080°C at a heating rate of 4°C / min in a nitrogen atmosphere, and then to 1150°C at a heating rate of 7°C / min, and kept at this temperature for 8 hours. After carbonization, the metal-doped graphite material was obtained after cooling.
[0106] The metal-doped graphite material was mixed in a solid phase mixer at 25 Hz and passed through a 350-mesh sieve to obtain a final metal-doped graphite composite material.
[0107] The metal-doped graphite composite material of this comparative example has a D50 of 6.9 μm.
[0108] Comparative Example 3
[0109] 3 kg of polyacrylic acid, 7 kg of deionized water and 0.015 kg of ammonium persulfate were mixed to obtain a polyacrylic acid solution with a concentration of 30%;
[0110] 50kg fixed carbon content is 99.99%, D50 particle size is 6.5μm, tap density is 0.79g / cm 3 , specific surface area is 11.85m 2 / g natural graphite, 5.56kg polyacrylic acid solution with a concentration of 30%, and 50kg deionized water were mixed uniformly at a rotation speed of 300rpm;
[0111] The mixed slurry was dried using a high-speed centrifugal spray dryer with an inlet temperature of 200°C, an outlet temperature of 150°C, and a rotation speed of 20000 rpm to obtain a coated natural graphite negative electrode material; then the obtained 7 μm coated natural graphite negative electrode material was heated from room temperature to 1080°C at a heating rate of 4°C / min under a nitrogen atmosphere, and then heated to 1150°C at a heating rate of 7°C / min, and kept warm for 8 hours. After carbonization, cooling was completed to obtain a carbon-coated graphite material;
[0112] The carbon-coated graphite material obtained after carbonization was mixed in a solid phase mixer at 25 Hz and passed through a 350-mesh sieve to obtain the final carbon-coated graphite material.
[0113] The carbon-coated graphite material of this comparative example has D50=7.2 μm.
[0114] Effect Example
[0115] The natural graphite negative electrode materials prepared in each embodiment and each comparative example were used as negative electrode materials to prepare 2032 type button batteries, and the specific steps were as follows:
[0116] Natural graphite material, conductive agent SP, dispersant CMC, and binder AONE are mixed in a mass ratio of 96:1:0.5:2.5, and water is used as a solvent to prepare a negative electrode slurry; the negative electrode slurry is coated on a copper foil, a lithium sheet is used as a counter electrode, and a Celgard2400 microporous polypropylene membrane is used as a separator to prepare a button battery.
[0117] The prepared button battery was subjected to charge and discharge cycles, and the charge and discharge conditions were as follows:
[0118] The electrochemical performance test was carried out on a blue battery tester. The test conditions were 25°C, the charge and discharge voltage range was 0 to 4.5V, and the charge and discharge rate was 0.1C. At the same time, its rate performance was tested, charging at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C, and discharging at 0.1C. The discharge capacity of the battery was tested under different charging modes. Five button batteries were prepared for each group of experimental samples, and the average value was finally taken. The results are shown in Table 1 below.
[0119] Table 1 Electrochemical performance test results
[0120]
[0121] Test result analysis:
[0122] It can be seen from Examples 1 and 2 that large-particle graphite will make the transmission path of lithium ions longer, affecting the rate performance. In addition, large-particle natural graphite is more difficult to coat, resulting in poor coating uniformity, which in turn leads to reduced rate performance.
[0123] It can be seen from Examples 1 and 3 that too much polyacrylic acid will result in an overly thick coating layer, an incomplete carbonization process, and the polyacrylic acid is not conductive, which affects the rate performance.
[0124] It can be seen from Example 1 and Example 5 that an excessive amount of molybdate will cause metal ions to agglomerate and form an uneven coating layer, which affects the rate performance.
[0125] It can be seen from Example 1 and Comparative Example 1 that when the carbon source is replaced with asphalt, the rate performance decreases significantly.
[0126] It can be seen from Example 1 and Comparative Examples 2 and 3 that the combined use of polyacrylic acid and ammonium molybdate can improve the rate performance.
Claims
1. A method for preparing a metal-doped carbon-coated graphite composite material, characterized in that: It includes the following steps: (1) subjecting the first mixed solution to a first heat treatment to obtain a carbon-coated graphite material; The first mixed solution comprises a carbon source, graphite and a first solvent, wherein the carbon source is a high molecular polymer carbon source, and the first solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent; The mass ratio of the graphite to the carbon source is 100:(1-10); (2) subjecting the second mixed solution to a second heat treatment to obtain a metal-doped carbon-coated graphite composite material; The second mixed solution includes the carbon-coated graphite material, a transition metal salt and water; The mass ratio of the carbon-coated graphite material to the transition metal salt is 100:(0.7-8).
2. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: In step (1), the polymer carbon source is one or more of polyacrylic acid, polystyrene, polyvinyl alcohol, polyamide, polymethyl methacrylate, polytetrafluoroethylene and polyurethane; Preferably, the molecular weight of the polymer carbon source is 10000-100000, for example 30000; Preferably, when the polymer carbon source is polyacrylic acid, the preparation method of polyacrylic acid comprises: mixing acrylic acid monomer, a second solvent and an initiator and reacting them to obtain polyacrylic acid; the second solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent; More preferably, the preparation method of polyacrylic acid meets one or more of the following conditions: a. The initiator is one or more of ammonium persulfate, potassium persulfate, azobisisobutyronitrile, benzoyl peroxide; b. The mass ratio of the initiator to the acrylic acid monomer is (0.5~2):100, for example 1:200; c. The mass ratio of the acrylic acid monomer to the third solvent is 1:(1-10), for example 1:2.3; d. The alcohol organic solvent is methanol and / or ethanol; e. The ketone organic solvent is methyl ethyl ketone; f. The ether organic solvent ethylene glycol monomethyl ether; g. The reaction temperature is 60 to 90 ° C; h. The reaction time is 2 to 6h; i. After the reaction is completed, the steps of filtering and drying are further included; the filtration is preferably suction filtration; the drying temperature is preferably 60-90°C; the drying time is preferably 15-25h.
3. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: Step (1) satisfies one or more of the following conditions: a. The mass ratio of the graphite to the carbon source is 100:(2-7), preferably 100:(2-5), for example 50:1.67 or 50:3.34; b. The graphite is spherical graphite, and the D50 particle size of the spherical graphite is preferably 4 to 20 μm, more preferably 6 to 10 μm; the tap density of the spherical graphite is preferably 0.6 to 1.0 g / cm 3 , more preferably 0.7~0.9g / cm 3 The specific surface area of the spherical graphite is preferably 6.0~15.0m 2 / g, preferably 10.0~13.0m 2 / g; the fixed carbon content of the graphite is preferably ≥99.95%; c. The graphite is natural graphite or artificial graphite; d. The carbon source is a polymer carbon source solution formed by a polymer carbon source and a third solvent, wherein the third solvent is one or more of water, an alcohol organic solvent, a ketone organic solvent and an ether organic solvent; the alcohol organic solvent is preferably methanol and / or ethanol; the ketone organic solvent is preferably methyl ethyl ketone; the ether organic solvent is preferably ethylene glycol monomethyl ether; the content of the polymer carbon source in the polymer carbon source solution is preferably 30-40%, for example 30%, where % refers to the mass proportion of the polymer carbon source in the polymer carbon source solution; e. The mass ratio of the first solvent to the graphite is (0.5-10):1, for example 1:1; f. In the first solvent, the alcohol organic solvent is methanol and / or ethanol; g. wherein the first solvent, the ketone organic solvent is methyl ethyl ketone; h. The first solvent, the ether organic solvent ethylene glycol monomethyl ether; i. The method for preparing the first mixed solution comprises: mixing the carbon source, the graphite and the first solvent and stirring; the stirring speed is preferably 200-600 rpm, more preferably 300-500 rpm; the stirring time is preferably 30-120 min, for example 90 min.
4. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: Step (1) satisfies one or more of the following conditions: a. The temperature of the first heat treatment is 1000~1500 ℃, preferably 1000~1200 ℃, for example 1150 ℃; b. The first heat treatment is heated in two stages, the first stage is preferably heated from room temperature to 900-1300°C, for example, 1080°C; the second stage is preferably heated from 900-1300°C to 1000-1500°C, for example, 1150°C; the first stage heating rate is preferably 3-25°C / min, for example, 4°C / min; the second stage heating rate is preferably 2-10°C / min, for example, 7°C / min; c. The first heat treatment is heated to the final temperature and the holding time is 6 to 10h, for example 8h; d. The first heat treatment is performed in an inert protective gas, wherein the protective gas is nitrogen or argon.
5. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: The mixed solution further comprises a drying step before the first heat treatment; preferably, the drying is spray drying; More preferably, the spray drying adopts a high-speed centrifugal spray dryer; the inlet temperature of the high-speed centrifugal spray dryer is preferably 50~400℃, more preferably 100~300℃, for example 200℃; the outlet temperature of the high-speed centrifugal spray dryer is preferably 50~200℃, more preferably 50~100℃, for example 150℃; the rotation speed of the high-speed centrifugal spray dryer is preferably 5000~40000rpm, more preferably 10000~30000rpm, for example 20000 rpm.
6. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: Step (2) satisfies one or more of the following conditions: a. The mass ratio of the carbon-coated graphite material to the transition metal salt is 100:(0.8~3), for example 50:0.45 or 50:0.9; b. The transition metal salt is a transition metal sulfate, a transition metal chloride or a transition metal ammonium salt, the transition metal sulfate is preferably one or more of nickel sulfate, cobalt sulfate, iron sulfate and titanium sulfate, the transition metal chloride is preferably titanium tetrachloride, and the transition metal ammonium salt is preferably ammonium molybdate; c. The method for preparing the second mixed solution comprises: mixing the transition metal salt with the water to obtain a transition metal salt solution, and mixing the transition metal salt solution with the carbon-coated graphite material to obtain the second mixed solution; Preferably, the carbon-coated graphite material and the transition metal salt solution are mixed by stirring; the stirring speed is preferably 200-600 rpm, more preferably 300-500 rpm; the stirring time is preferably 30-120 min, for example 90 min; Preferably, the content of the transition metal salt in the transition metal salt solution is 2.5-7%, such as 3% or 6%, where % refers to the mass proportion of the transition metal salt in the transition metal salt solution.
7. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: Step (2) satisfies one or more of the following conditions: a. The temperature of the second heat treatment is 800 to 1500 ° C, preferably 1000 to 1200 ° C, for example 1150 ° C; b. The heating of the second heat treatment is a two-stage heating, the first stage heating is preferably from room temperature to 700-1200°C, for example, 1080°C; the second stage heating is preferably from 700-1200°C to 800-1500°C, for example, 1150°C; the heating rate of the first stage is preferably 3-25°C / min, for example, 4°C / min; the heating rate of the second stage is preferably 2-10°C / min, for example, 7°C / min; c. The second heat treatment is heated to the final temperature and the holding time is 6 to 10h, for example 8h; d. The second heat treatment is performed in an inert protective gas, wherein the protective gas is nitrogen or argon.
8. The method for preparing the metal-doped carbon-coated graphite composite material according to claim 1, characterized in that: The second heat treatment further includes a drying step; preferably, the drying is spray drying; more preferably, the spray drying adopts a high-speed centrifugal spray dryer; the inlet temperature of the high-speed centrifugal spray dryer is preferably 50-400°C, more preferably 100-300°C, for example 200°C; the outlet temperature of the high-speed centrifugal spray dryer is preferably 50-200°C, more preferably 50-100°C, for example 150°C; the rotation speed of the high-speed centrifugal spray dryer is preferably 5000-40000 rpm, more preferably 10000-30000 rpm, for example 20000 rpm; And / or, a screening step is further included after the second heat treatment; preferably, the sieve is 300-350 mesh; preferably, a mixing step is also included before the screening, and the mixing method comprises: placing the material obtained by the second heat treatment in a mixer for mixing, and the frequency of the mixer is 20-30 Hz, for example, 25 Hz.
9. A metal-doped carbon-coated graphite composite material prepared by the method for preparing a metal-doped carbon-coated graphite composite material according to any one of claims 1 to 8; Preferably, the particle size of the metal-doped carbon-coated graphite composite material is 7-15 μm, such as 7.4 μm, 7.5 μm, 7.6 μm or 13.7 μm.
10. Use of the metal-doped carbon-coated graphite composite material as claimed in claim 9 as a negative electrode material in a lithium-ion battery.
Citation Information
Patent Citations
Preparation method of high-energy-density fast-charging negative electrode material
CN116588924A
Novel monatomic doped graphite negative electrode material for lithium ion battery and preparation method of novel monatomic doped graphite negative electrode material
CN118658989A